Effect of Green Manufacturing on Operational Performance of Manufacturing Firms in Mombasa County, Kenya - Eric Mutie Musau; Kingsford Rucha (European Scientific Journal, ESJ, 2021)
This paper focuses on investigating the effect of green manufacturing on operational performance of manufacturing firms. The study adopted crosssectional survey design and data was collected across all the 61 manufacturing firms listed by KAM in 2019 through questionnaires. The study used Regression Model technique to analyze the quantitative data and validate the developed research model. Green manufacturing was found to have a positive effect on operational performance. Green product design and development, GSCM, and efficient processes had significant effect in enhancing operational performance while end-of-life product management was found to have insignificant relationship with operational performance.